## Answer :

Let's break down the information provided:

1. The low temperature is [tex]\(-4^\circ F\)[/tex].

2. The difference between the high temperature [tex]\(h\)[/tex] and the low temperature is [tex]\(6^\circ\)[/tex].

We start with the equation given in the problem:

[tex]\[ h - (-4) - 6 = 0 \][/tex]

Solving this equation step-by-step:

1. Simplify the expression within the equation:

[tex]\[ h - (-4) \text{ is equivalent to } h + 4 \][/tex]

So, substituting [tex]\(h - (-4)\)[/tex] with [tex]\(h + 4\)[/tex], the equation becomes:

[tex]\[ h + 4 - 6 = 0 \][/tex]

2. Combine like terms:

[tex]\[ h + 4 - 6 = h - 2 \][/tex]

So the equation now is:

[tex]\[ h - 2 = 0 \][/tex]

3. Solve for [tex]\(h\)[/tex]:

[tex]\[ h - 2 = 0 \implies h = 2 \][/tex]

Therefore, the high temperature in the town that day was [tex]\(2^\circ F\)[/tex].

So, the correct answer is:

[tex]\[ \boxed{2} \][/tex]